2020
DOI: 10.1177/2040206620983780
|View full text |Cite
|
Sign up to set email alerts
|

Gallium maltolate has in vitro antiviral activity against SARS-CoV-2 and is a potential treatment for COVID-19

Abstract: Background Gallium has demonstrated strong anti-inflammatory activity in numerous animal studies, and has also demonstrated direct antiviral activity against the influenza A H1N1 virus and the human immunodeficiency virus (HIV). Gallium maltolate (GaM), a small metal-organic coordination complex, has been tested in several Phase 1 clinical trials, in which no dose-limiting or other serious toxicity was reported, even at high daily oral doses for several months at a time. For these reasons, GaM may be considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Vanadium can stimulate the activation of T cells [116], and bismuth has an inhibitory effect on helix unwinding and ATPase activity of SARS-CoV-2 nsp13 [27], so these metals might be useful in the treatment of COVID-19. About gallium there are two ideas, some studies believe that gallium has an anti-inflammatory and antiviral activity against SARS-CoV-2 and inhibits viral replication [119][120][121][122][123], but other studies believe that there is no relation between gallium uptake and COVID-19 related disorders [118]. Palladium and some Schiff base complexes of titanium have an affinity to the main protease of SARS-CoV-2, so they may be useful in vaccine production [127,128].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanadium can stimulate the activation of T cells [116], and bismuth has an inhibitory effect on helix unwinding and ATPase activity of SARS-CoV-2 nsp13 [27], so these metals might be useful in the treatment of COVID-19. About gallium there are two ideas, some studies believe that gallium has an anti-inflammatory and antiviral activity against SARS-CoV-2 and inhibits viral replication [119][120][121][122][123], but other studies believe that there is no relation between gallium uptake and COVID-19 related disorders [118]. Palladium and some Schiff base complexes of titanium have an affinity to the main protease of SARS-CoV-2, so they may be useful in vaccine production [127,128].…”
Section: Discussionmentioning
confidence: 99%
“…And at last, it is observed that gallium has an anti-inflammatory effect which is effective against hyperinflammatory signs observed in harsh cases of COVID-19 patients which is similar to septic shock [121,122]. GaM inhibited replication of virus dose dependently with a concentration of 14 μM, which replication inhibited by 50% [123].…”
Section: Galliummentioning
confidence: 98%
“…At doses up to 200 mM, the gallium maltolate was not hazardous to the cells (the function of cells at 200 mM was 109(3)% compared with the control cells) ( Figure S6 ). [ 128 ] The EC50 data was estimated by an inhibitor vs. balanced response, movable slope equation: Y = 100/(1 + 10exp((LogEC50 − X) × HillSlope)). …”
Section: In Vitro and In Vivo Potency Of Metallo-compounds Against Sa...mentioning
confidence: 99%
“…At present, two methods are used to discover potential metal-based drugs for COVID-19: repurposing existing medications and developing new drugs [ 27 , 28 ]. These metallodrugs might directly inhibit virus replication [ 68 , 69 ], prevent viruses from entering cells [ 63 ], or inhibit the activity of critical enzymes in the process of virus replication [ 34 36 , 70 , 71 ]. Furthermore, the combination of antiviral drugs and metals can be more effective.…”
Section: Metal-related Prevention and Treatment Strategiesmentioning
confidence: 99%
“…Pectol et al [ 104 ] proved that dinitroso-iron complexes (DNICs) could be used as inhibitors of SARS-CoV-2 M pro through computer prediction and external studies. In addition, Bernstein and Zhang [ 69 ] used gallium maltolate (GaM) to treat SARS-CoV-2-infected Vero E6 cells to evaluate the antiviral ability. Its ability to prevent virus replication has been proven, and its efficacy is related to dosage.…”
Section: Metal-related Prevention and Treatment Strategiesmentioning
confidence: 99%